The Criminal Law and Criminological Aspects of Sexual Violence in the Republic of Serbia - Vujičić, Nikola (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Sexual violence in the Republic of Serbia, if we look at statistics, is not a big problem. Crimes against sexual freedom, in percentage terms, in the Republic of Serbia participating in the structure of a very low crime, with a little less than 1%, compared to the total number of criminal charges for all crimes. Also, when we compare the Republic of Serbia with other European countries, it is clear that it is among the countries with the lowest rate, along with Turkey, Armenia, Croatia, Greece, and Poland. The average rate per 100,000 population in the period 2007-2011. year is: for sexual assault (7), for rape (1.1). As in other countries, the problem with these offences is the high dark figure of crime. The Council of Europe Convention on preventing and combating violence against women and domestic violence (CETS No.210) - Istanbul Convention, which was ratified by the Republic of Serbia, opens a series of questions on the plan of regulation. The current criminal legislation will have to be harmonized with that Convention. The problem is particularly common in the demarcation of the criminal offence of Rape and the criminal offense of Prohibited Sexual Acts. Society reacts differently to sexual violence, and because the victims of this form of violence are a particularly weak group, they need help. Help and support victims receive from the authorities of formal social control and from the non-governmental sector. These organizations in practice, above all, provide emotional support to victims, and refer victims to other services and professionals who can provide them with medical, legal or other assistance. Unlike most European countries, the Republic of Serbia has not adopted the Victims of Crime Assistance Act. The Republic of Serbia must adopt that Law and, on the basis of it, establish a state body and a fund for victims, which would be a conditio sine qua non of development services for the victims, who have shown that often contribute to a better "recovery" of victims of sexual violence from any other form of social reaction.